Chronic pancreatitis and nutritional support. (February 2023) - Campagnola, Pietro; de Pretis, Nicolò; Zorzi, Alberto; Caldart, Federico; Frulloni, Luca
Abstract: Malnutrition in patients with chronic pancreatitis is common, but its evaluation is often missed in clinical practice. Pancreatic exocrine insufficiency is the single most important cause of malnutrition; therefore, it needs to be screened for and treated appropriately. Specific diet regimens in patients suffering from chronic pancreatitis are rarely reported in the literature. Patients suffering from chronic pancreatitis have a higher demand for energy but a lower caloric intake secondary to pancreatic exocrine insufficiency, combined with the malabsorption of liposoluble vitamin and micronutrients, which needs be corrected by appropriate dietary counselling. Diabetes is frequently observed in chronic pancreatitis and classified as type 3c, which is characterized by low levels of both serum insulin and glucagon; therefore, there is a tendency towards hypoglycaemia in patients treated with insulin. Diabetes contributes to malnutrition in chronic pancreatitis. Strategies to treat exocrine and endocrine insufficiency are important to achieve better control of the disease.